PREFERENCES OF INFORMATION SOURCES IN VETERINARY SCIENCE IN INDIA: BEST-WORST SCALING ANALYSIS - Kutty Kumar; B. Rambabu Naik (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study examines the preferences of information sources among veterinary science professionals in India, employing a Best-Worst Scaling analysis to identify the most and least favoured sources, as well as the constraints faced in accessing these resources. Conducted through an online survey in 2024, the research gathered responses from 142 veterinary professionals, predominantly male (88.73%). Key findings reveal that the internet and training courses are the most preferred information sources, while traditional resources like CD databases are least favoured. Constraints such as information overload and inadequate infrastructure significantly hinder effective information access. The study highlights gender disparities in information source preferences and emphasizes the need for improved access to information and resources in the veterinary field.